Adsorption behavior and mechanism of 9-Nitroanthracene on typical microplastics in aqueous solutions. (April 2020) - Zhang, Jinghua; Chen, Huangbo; He, Huan; Cheng, Xinying; Ma, Tao; Hu, Jiapeng; Yang, Shaogui; Li, Shiyin; Zhang, Limin
Abstract: Microplastics and Nitropolycyclic aromatic hydrocarbons (NPAHs) are two types of emerging pollutants that are strong potential threats to aquatic ecosystems and organisms. The adsorption of NPAHs on microplastics may explain the fate and effects of NPAHs in natural environments. In this study, the adsorption behavior of 9-Nitroanthrene (9-NAnt) on polyethylene (PE), polypropylene (PP) and polystyrene (PS) was investigated. Kinetic experiments revealed that 9-NAnt was inclined to be adsorbed onto microplastics, especially PE, which had a large adsorption amount of 734 μg g −1 . A linear isothermal model better described the isothermal adsorption process for 9-NAnt, which indicated that a hydrophobic distribution may be the main adsorption mechanism in an aqueous solution. Water environment factors, such as the pH and ionic strength, had negligible effects on the adsorption for PE. In contrast, alkaline and high ionic strength conditions resulted in the inhibition of adsorption of PP and PS. In addition, the particle size of microplastics was negatively correlated with the log Kd of 9-NAnt, and the performance of transient aging treatments on microplastics reduced their affinity for 9-NAnt, due to the addition of oxygen-containing functional groups. Above all, hydrophobic and electrostatic processes were the main adsorption mechanisms between microplastics and 9-NAnt. Graphical abstract: Image 1 Highlights: Polyethylene, Polypropylene and Polystyrene show high adsorption capacity for 9-NAnt. Adsorption of 9-NAnt on Polyethylene was generally not affected by pH and ionic strength. The adsorption of 9-NAnt were fitted well with quasi-second dynamic model. Hydrophobic interaction of 9-NAnt on microplastics was dominant adsorption mechanism. The ultraviolet aging process reduced the adsorption of 9-NAnt on microplastics.